Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 49922 by Pk1167156@gmail.com last updated on 12/Dec/18

Answered by tanmay.chaudhury50@gmail.com last updated on 12/Dec/18

∫((x^4 dx)/(x^4 (x^4 +(1/x^4 ))))  ∫(dx/(x^4 +(1/x^4 )))  ∫(dx/((x^2 +(1/x^2 ))^2 −2))  (1/2)∫(((1−(1/x^2 )+1+(1/x^2 )))/((x^2 +(1/x^2 ))^2 −2))  =(1/2)[∫((d(x+(1/x)))/({(x+(1/x))^2 −2}^2 −2))+∫((d(x−(1/x)))/({(x−(1/x))^2 +2}^2 −2))]  =(1/2)[∫(dp/((p^2 −2)^2 −2))+∫(dq/((q^2 +2)^2 −2))]  =(1/2)[∫(dp/(p^4 −4p^2 +2))+∫(dq/(q^4 +4q^2 +2))]  =(1/2)[∫((1/p^2 )/(p^2 +(2/p^2 )−4))dp+∫((1/q^2 )/(q^2 +(2/q^2 )+4))]=(1/2)(I_1 +I_2 )  now solving I_1   ∫(([(1+((√2)/p^2 ))−(1−((√2)/p^2 ))]×(1/(2(√2))))/((p^2 +(2/p^2 ))−4))dp  =(1/(2(√2)))∫((d(p−((√2)/p)))/((p−((√2)/p))^2 +2(√2) −4))−(1/(2(√2)))∫((d(p+((√2)/p)))/((p+((√2)/p))^2 −2(√2) −4))  =(1/(2(√2)))∫((d(p−((√2)/p)))/((p−((√2)/p))^2 −((√(4−2(√2)))  )^2 )) −(1/(2(√2)))∫((d(p+((√2)/p)))/((p+((√2)/p))^2 −((√(4+2(√2))) )^2 ))  =(1/(2(√2) ))×(1/(2((√(4−2(√2))))))×ln{(((p−((√2)/p))−(√(4−2(√2))))/((p−((√2)/p))+(√(4−2(√2)))))}−(1/(2(√2)))×(1/(2(√(4+2(√2))) ))ln{(((p+((√2)/p))−(√(4+2(√2))))/((p+((√2)/p))+(√(4+2(√2)))))}+c_1   p=(x+(1/x))  pls put p=x+(1/x)  nxt going to find I_2   I=(1/2)(I_1 +I_2 ) ←required answer...  now findngI_2   ∫((1/q^2 )/((q^2 +(2/q^2 ))+4))dq  =(1/(2(√2)))∫(((1+((√2)/q^2 ))−(1−((√2)/q^2 )))/((q^2 +(2/q^2 ))+4))dq  =(1/(2(√2)))∫((d(q−((√2)/q)))/((q−((√2)/q))^2 +2(√2) +4))−(1/(2(√2)))∫((d(q+((√2)/q)))/((q+((√2)/q))^2 +4−2(√2)))  =(1/(2(√2)))×(1/(√(4+2(√2))))tan^(−1) (((q−((√2)/q))/(√(4+2(√2)))))−(1/(2(√2)))×(1/(√(4−2(√2))))tan^(−1) (((q+((√2)/q))/(√(4−2(√2)))))+c_2   pls put q=(x−(1/x))  so I=(1/2)(I_1 +I_2 )

x4dxx4(x4+1x4)dxx4+1x4dx(x2+1x2)2212(11x2+1+1x2)(x2+1x2)22=12[d(x+1x){(x+1x)22}22+d(x1x){(x1x)2+2}22]=12[dp(p22)22+dq(q2+2)22]=12[dpp44p2+2+dqq4+4q2+2]=12[1p2p2+2p24dp+1q2q2+2q2+4]=12(I1+I2)nowsolvingI1[(1+2p2)(12p2)]×122(p2+2p2)4dp=122d(p2p)(p2p)2+224122d(p+2p)(p+2p)2224=122d(p2p)(p2p)2(422)2122d(p+2p)(p+2p)2(4+22)2=122×12(422)×ln{(p2p)422(p2p)+422}122×124+22ln{(p+2p)4+22(p+2p)+4+22}+c1p=(x+1x)plsputp=x+1xnxtgoingtofindI2I=12(I1+I2)requiredanswer...nowfindngI21q2(q2+2q2)+4dq=122(1+2q2)(12q2)(q2+2q2)+4dq=122d(q2q)(q2q)2+22+4122d(q+2q)(q+2q)2+422=122×14+22tan1(q2q4+22)122×1422tan1(q+2q422)+c2plsputq=(x1x)soI=12(I1+I2)

Commented by Pk1167156@gmail.com last updated on 12/Dec/18

thank you very much sir.

Commented by tanmay.chaudhury50@gmail.com last updated on 12/Dec/18

most welcome...

mostwelcome...

Terms of Service

Privacy Policy

Contact: info@tinkutara.com